PENGARUH TEKNIK PEMODELAN TERHADAP KETERAMPILAN MENULIS TEKS PROSEDUR KOMPLEKS SISWA KELAS XI SMKN 1 TAPAN - Utami, Mimi Putri; Thamsin, Andria Catri; Hafrison, Mohammad (Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2019)
ABSTRACT This article has been writing techniques influence modeling text writing skills against the complex procedure of grade XI 1 — Tapan. This research is quantitative research with quasi experiment method of the one group pretest-postest design. The data in this study is the writing skills test score of complex procedure text grade XI 1 — Tapan before and after using the technique of modeling. The data obtained through test performance.  Based on the results of data analysis, researchers concluded three things here; First, complex procedure text writing skills of students of Class XI 1 — Tapan before using the techniques of modelling are at Sufficient qualifications (62.02). Second, complex procedure text writing skills of students of Class XI — 1 using the technique of modeling after the Tapan is at Good qualifications (78.57). Third, based on the t-test, the alternative hypothesis (H1) are accepted on the degrees of confidence and degrees of freedom (dk) = (n-1) because thitung > ttabel (7.10 > 1.70). In other words, modeling techniques to complex procedures text writing skills of students of Class XI 1 — Tapan. Kata kunci: Teknik Pemodelan, Pengaruh, Keterampilan, Teks Prosedur Kompleks